Investigation of anti-osteoporosis mechanisms of Rehmanniae Radix Preparata based on network pharmacology and experimental verification - Li Ou; Wenqian Kang; Ziyi Liang; Feng Gao; Taiwei Dong; Peifeng Wei; Min Li (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Rehmanniae Radix Preparata (RRP) can effectively improve the symptoms of osteoporosis, but its molecular mechanism for treating osteoporosis is still unclear. The objective of this study is to investigate the anti-osteoporosis mechanisms of RRP through network pharmacology. Methods The overlapping targets of RRP and osteoporosis were screened out using online platforms. A visual network diagram of PPI was constructed and analyzed by Cytoscape 3.7.2 software. Molecular docking was used to evaluate the binding activity of ligands and receptors, and some key genes were verified through pharmacological experiments. Results According to topological analysis results, AKT1, MAPK1, ESR1, and SRC are critical genes for RRP to treat osteoporosis, and they have high binding activity with stigmasterol and sitosterol. The main signal pathways of RRP in the treatment of osteoporosis, including the estrogen signaling pathway, HIF-1 signal pathway, MAPK signal pathway, PI3K-Akt signal pathway. Results of animal experiments showed that RRP could significantly increase the expression levels of Akt1, MAPK1, ESR1, and SRC1 mRNA in bone tissue to increase bone density. Conclusion This study explained the coordination between multiple components and multiple targets of RRP in the treatment of osteoporosis and provided new ideas for its clinical application and experimental research.